Modernization Education System of Dayah Terpadu Al-Azhar - Nur, Ismet (International Journal for Educational and Vocational Studies, 2019)
The existence of dayahs in Central Aceh is an Islamic educational institution that contributes in influencing the religious life of the community, day by step the development of both the quantity and quality is increasing. This study aims to describe the modernization Education System of Dayah Terpadu Al-Azhar, includes sub-systems of dayah education. This research is a field research with a descriptive qualitative method using a phenomenological approach, the main data source of this study is the document, and the informants are leaders of dayah, teungku dayah, santri and community leaders. Modernization education system of Dayah Terpadu Al-Azhar is characterized by changes in objectives, teungku and santri dayah, implementation of an integrated curriculum, enriching the treasures of contemporary books, the use of active strategies and varied methods, development of the dayah environment, and evaluation of learning.